ElectroKitty: A Python Tool for Modeling Electrochemical Data Including Non-Langmuir Adsorption - Vodeb, Ožbej; Farinazzo Bergamo Dias Martins, Pedro; Strmčnik, Dušan; Hodnik, Nejc; Gaberšček, Miran (ACS electrochemistry, 2025)
The use of simulation and various forms of data analysis is becoming more frequent in all areas of electrochemistry. To support this, we have created ElectroKitty, a Python package that can simulate complex reaction pathways. Since experimental data often exhibits non-idealities with adsorbed species, we have programmed ElectroKitty to incorporate such corrections. To demonstrate the versatility of our package we selected four common reaction pathways and validated it against an established simulator. We also demonstrate the Frumkin isotherm and how ElectroKitty can reproduce it. In addition, to demonstrate the more advanced features of our package, we used ElectroKitty to simulate OH adsorption on a Pt(111) surface using a straightforward model.